Endothelial Arf6 sustains electrical signaling and cerebral blood flow in mice through PIP 2 -dependent activation of Kir2.1 channels - Maria F. Noterman-Soulinthavong; María Sancho; Saúl Huerta de la Cruz; Michael Yarboro; Maurizio Mandalà; Masayo Koide; Nathalie Beaufort; Katalin Todorov-Völgyi; Emma Moreland; David Hill-Eubanks; Martin Dichgans; Mark T. Nelson (Proceedings of the National Academy of Sciences, 2026)
Brain capillaries sense neural activity and direct blood flow to active regions—a process termed neurovascular coupling that underlies activity-dependent increases in local perfusion (functional hyperemia). A key contributor to functional hyperemic responses is the capillary endothelial cell (cEC) inward rectifier K + (Kir2.1) channel, which, when activated by neuronal activity–derived extracellular K + , initiates vasodilatory electrical signals that propagate through the vascular network. Kir2.1 channel function requires continual production of its lipid cofactor, phosphatidylinositol-4,5-bisphosphate (PIP 2 ), and is compromised in mouse models of cerebral small vessel (cSVD). Although decreased PIP 2 availability is a common feature of cSVDs, mechanisms underlying PIP 2 synthesis remain poorly understood. We hypothesized that Arf6, a small GTPase expressed in cECs that stimulates PIP 2 production, is critical for this process. Using patch-clamp electrophysiology, we demonstrate that inhibiting Arf6 activity progressively decreased cEC Kir2.1 channel activity. This deficit manifested as loss of capillary-to-arteriole electrical signaling in isolated vessels and diminished functional hyperemia in vivo. Exogenously provided PIP 2 restored Kir2.1 currents and functional hyperemia after Arf6 inhibition or genetic knockdown. Collectively, our data suggest that cEC Arf6 sustains Kir2.1 activity by maintaining PIP 2 levels and demonstrate that diminished PIP 2 synthesis is sufficient to impair functional hyperemia. Furthermore, we identify Arf6 as a mechanistic link between PIP 2 production and endothelial electrical signaling, highlighting Arf6 as a potential therapeutic target for restoring functional hyperemia.